1970
DOI: 10.1073/pnas.67.1.247
|View full text |Cite
|
Sign up to set email alerts
|

5-Bromodeoxyuridine-Induced Differentiation of a Neuroblastoma

Abstract: Abstract. 5-Bromodeoxyuridine induces the differentiation of mouse neuroblastoma C1300 to cells that morphologically resemble mature neurons. The induced differentiation can take place in the absence of DNA synthesis. This suggests that the halogenated pyrimidine need not be incorporated into DNA to alter the phenotype of the cell.It has been demonstrated that a cloned tissue-culture line of mouse neuroblastoma C1300 can be induced to "differentiate" in vitro.' When the cells are grown in suspension in Petri d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(38 citation statements)
references
References 8 publications
(1 reference statement)
2
36
0
Order By: Relevance
“…If globin mRNA synthesized by BrU-treatect cells contained frequent errors in transcription so that one base in 50 was incorrectly transcribed, a difference in the stability of duplexes formed between cDNA and globin mRNA from cells treated with (CH3)2S0 and with BrdU and (CH3)2S0 would have been detected (22). No An unusual observation has been the report that BrdU induces the differentiation of neuroblastoma cells in vitro, an effect independent of the incorporation of DNA (5). This latter observation is contrary to other studies which indicated that BrdU incorporation into DNA was essential for its biological effects (1,2,6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If globin mRNA synthesized by BrU-treatect cells contained frequent errors in transcription so that one base in 50 was incorrectly transcribed, a difference in the stability of duplexes formed between cDNA and globin mRNA from cells treated with (CH3)2S0 and with BrdU and (CH3)2S0 would have been detected (22). No An unusual observation has been the report that BrdU induces the differentiation of neuroblastoma cells in vitro, an effect independent of the incorporation of DNA (5). This latter observation is contrary to other studies which indicated that BrdU incorporation into DNA was essential for its biological effects (1,2,6).…”
Section: Resultsmentioning
confidence: 99%
“…5-Bromo-2 '-deoxyuridine (BrdU) provides a tool for investigating some of the molecular events involved in ontogenesis as well as oncogenesis, for it affects tissues as dissimilar as muscle cells of chick embryo (1), mammary tissue of pregnant mice (2), and malignant cells (3)(4)(5)(6)(7). The effects on each of these systems are considered to be specific and nonrandom.…”
mentioning
confidence: 99%
“…This analogue can promote neurite extension in the absence of DNA synthesis, however (Schubert and Jacob, 1970).…”
Section: B Neuroblasto Ma Cellsmentioning
confidence: 99%
“…In contrast, exposure of BrdU-resistant, thymidine kinase-NOTES negative (TK-) Friend cells to BrdU results in induction or potentiation of DMSO-induced differentiation (6). BrdU has been shown to have a selective effect upon a number of differentiating systems (1, 4, 13, 17, 22-24, 29, 30, 33) under conditions in which mutagenicity can be excluded as a mechanism (for review, see reference 25), and occasionally in which these effects are not related to the incorporation of the analog into DNA (5,6,24,26). Similarly, purine analogs have been shown to induce differentiation in purine analog-resistant Friend cells, whereas hypoxanthine is an effective inducer of wild-type and both purine and pyrimidine analog-resistant Friend erythroleukemia cells (12; unpublished data).…”
mentioning
confidence: 99%